Software-Intensive Systems and New Computing Paradigms - Wirsing, Martin (Springer, 2017)
To identify the emergent trends in software-intensive and distributed and decentralized computer systems and their impact on the Information Society in the next 10--15 years, the European Commission has established two Coordinated Actions: Initially the project `Beyond the Horizon' and then, starting in 2006, the project `InterLink'.